Physical Simulation Based on Dynamic Transformation Under Hot Plate Rolling of a Nb-Microalloyed Steel - Ferreira, João Carlos; de Sousa Machado, Francisco Romario; Aranas, Clodualdo; Siciliano, Fulvio; Pasco, Jubert; Reis, Gedeon Silva; Pedrosa de Miranda, Edson Jansen; Macêdo Paiva, Antônio Ernandes; Rodrigues, Samuel Filgueiras (Frontiers in Materials, 2021)
The deformation of austenite in the single austenite phase field leads to the formation of Widmanstätten ferrite plates, which eventually merge into polygonal ferrite grains at higher strains. This unusual metallurgical process, known as dynamic transformation (DT), mainly occurs via a displacive mechanism. The metastable austenite phase undergoes reverse transformation when the temperature is held above the Ae3 via a diffusion process. These phenomena affect the rolling load during high-temperature plate rolling, which was investigated in this work. Therefore, a linepipe X70 steel was studied under plate rolling with two-pass roughing and seven-pass finishing strains of 0.4 and 0.2, respectively, applied at strain rate of 1 s-1 and interpasses of 10, 20, and 30 seconds. The samples were cooling down during deformation, which mimics the actual industrial hot rolling. It was observed that the alloy softens as the hot rolling progresses, as depicted by flow curves and mean flow stress plots, which are linked to the combined effects of dynamic transformation and recrystallization. The former initially occurs at lower strains, followed by the latter at higher strains. The critical strain to DT was affected by the number of passes and temperature of deformation. Shorter interpass time allows higher amounts of ferrite to form due to higher retained work hardening. Similarly, the closer the deformation temperature to the Ae3 permits a higher DT ferrite fraction. The information from this work can be used to predict the formation of phases immediately after hot rolling and optimize models applied to the accelerated cooling.